ANTIHYPERTENSIVE THERAPY TACTICS IN HYPERTENSIVE CRISE COMPLICATED BY HAEMORRHAGIC STROKE - G. E. Gendlin; A. V. Melekhov; Yu. I. Ostrovskaya; G. I. Storozhakov; K. M. Gorshkov; D. B. Sokolan; I. S. Aliev; I. A. Voropaeva (Кардиоваскулярная терапия и профилактика)
Aim. To identify the optimal tactics of antihypertensive therapy (AHT) in patients with hypertensive crise (HC), complicated by haemorrhagic stroke (HS).Material and methods. Forty patients aged 46–87 years, who were hospitalised with HC and HS as its complication.Results. All patients were divided into two groups, according to the median levels of systolic blood pressure (SBP) at 20 minutes after the start of the treatment: SBP >161 mm Hg vs. SBP <161 mm Hg. A significantly better survival was observed in patients with a higher degree of the 20-minute SBP eduction. In addition, patients were divided into tertiles of the 20-minute SBP levels. Participants with SBP 136–149 mm Hg demonstrated a significantly better survival. The degree of SBP reduction at 220 minutes was not significantly associated with survival. Furthermore, the patients were divided into two groups by the rate of SBP reduction. Faster rates were associated with a better survival (PGW=0,002). The second part of the study was focused on the assessment of effectiveness and safety of urapidil hydrochloride (Ebrantil). The patients were randomised into two groups: one group was administered Ebrantil, while another received the standard neuroresuscitation unit treatment. Ebrantil therapy demonstrated a fast and effective SBP reduction at 20 minutes, which was also associated with a better survival.Conclusion. We identified optimal, associated with a better survival, BP levels (136–149 mm Hg) for patients with HC complicated by HS. Target BP levels should be achieved within 20 minutes, as a slower BP reduction is linked to a worse prognosis. Ebrantil is an effective and safe antihypertensive medication.